2020
DOI: 10.1186/s11689-020-09331-4
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth-enabled behavioral treatment for problem behaviors in boys with fragile X syndrome: a randomized controlled trial

Abstract: Background Children with fragile X syndrome (FXS) are at increased risk for exhibiting problem behaviors such as aggression and self-injury. However, many children with FXS have limited access to behavioral treatments that have known efficacy due to the low availability of treatment providers and the wide geographical dispersion of families with FXS across the country. Telehealth may offer a cost-effective and practical solution to overcome these significant barriers. We examined the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…The most common version of telehealth services represented in the published literature is a caregiver telehealth coaching model, which involves a clinician providing training via synchronous videoconferencing to another person (e.g., parent, teacher, technician) at a distant site to deliver services in‐person to the client (Council of Autism Service Providers [CASP], 2020a; Lerman et al, 2020). This model has been used for functional behavior assessments (Barretto et al, 2006; Benson et al, 2018; Boisvert et al, 2010), preference assessments (Higgins et al, 2017), behavior reduction procedures (Hall et al, 2020; Lindgren et al, 2016; Monlux et al, 2019; Suess et al, 2016; Suess et al, 2020; Unholz‐Bowden et al, 2020; Wacker et al, 2013a; Wacker et al, 2013b), and interventions to build language, social, and daily living skills (Akemoglu et al, 2020; Barkaia et al, 2017; Ferguson et al, 2019; Ingersoll et al, 2016; McLay et al, 2020; Wainer & Ingersoll, 2015). A telehealth model commonly applied in clinical settings is a partial in‐person telehealth model whereby ABA services are rendered in‐person by a trained technician, with clinical oversight provided by a behavior analyst via real‐time, synchronous videoconference modality (CASP, 2020b).…”
mentioning
confidence: 99%
“…The most common version of telehealth services represented in the published literature is a caregiver telehealth coaching model, which involves a clinician providing training via synchronous videoconferencing to another person (e.g., parent, teacher, technician) at a distant site to deliver services in‐person to the client (Council of Autism Service Providers [CASP], 2020a; Lerman et al, 2020). This model has been used for functional behavior assessments (Barretto et al, 2006; Benson et al, 2018; Boisvert et al, 2010), preference assessments (Higgins et al, 2017), behavior reduction procedures (Hall et al, 2020; Lindgren et al, 2016; Monlux et al, 2019; Suess et al, 2016; Suess et al, 2020; Unholz‐Bowden et al, 2020; Wacker et al, 2013a; Wacker et al, 2013b), and interventions to build language, social, and daily living skills (Akemoglu et al, 2020; Barkaia et al, 2017; Ferguson et al, 2019; Ingersoll et al, 2016; McLay et al, 2020; Wainer & Ingersoll, 2015). A telehealth model commonly applied in clinical settings is a partial in‐person telehealth model whereby ABA services are rendered in‐person by a trained technician, with clinical oversight provided by a behavior analyst via real‐time, synchronous videoconference modality (CASP, 2020b).…”
mentioning
confidence: 99%
“…The Health Resources and Services Administration defines telehealth as the "use of electronic information and telecommunication technologies to support long-distance clinical health care, patient and professional health related education, public health and health administration" (Health Information Technology, 2019, Telehealth section, para.1). The research on telehealth in behavior analysis has demonstrated its application and success with parent training and parent-implemented services (Benson et al, 2018;Gerow et al, 2021;Ingersoll et al, 2016;Schieltz & Wacker, 2020;Wainer & Ingersoll, 2015), conducting functional analyses (Gerow et al, 2021;Schieltz & Wacker, 2020), teaching new operants (Pellegrino & DiGennaro Reed, 2020), behavior management (Hall et al, 2020;Monlux et al, 2019) and staff training (Piazza et al, 2021). Recent research has also demonstrated that the delivery of behavior-analytic services via telehealth is effective for some individuals diagnosed with autism spectrum disorder (Pollard et al 2021) and that it is possible for an organization to successfully transition to telehealth services (Crockett et al, 2020).…”
mentioning
confidence: 99%
“…Moreover, continued implementation of behavioral interventions that target child characteristics such as those found to relate to maternal well-being and parenting stress in the present sample (e.g., externalizing behaviors like irritability, aggression, etc.) are paramount to the meeting the needs of the whole family especially when parents are included in their child's treatment plan [e.g., through parent mediated interventions; (102,103)].…”
Section: Profiles Of Maternal Well-beingmentioning
confidence: 99%